EFFECTS ON THE DEVELOPMENT OF THE NESTS OF Polistes erythrocephalus (Hymenoptera: Vespidae) AS A RESULT OF THE APPLICATION OF TWO CHITIN INHIBITORS, ONE SULPHONATE AND ONE ORGANOPHOSPHORATE - VALENCIA, EDISON; VARGAS, HECTOR A.; SEGURA, FANOR (Revista Colombiana de Entomología, 1990)
Through the one month-cage trials for Polistes erythrocephalus (Latreille) it was possible to determine that the general development of the nests where the adults were offered with Spodoptera frugiperda (J.E. Smith) larvae treated with TFB and DES, was inferior to those nests treated with endosulfan and those of the control. On the other hand, under the chitin inhibitortreatmensts, some malformed adults appeared approximately two weeks after the beginning of the trial; these adults had very short, weak, or rolled wings and presented no longer survivorship. On those nests treated with monocrotophos, there was a total mortal ity of the adults 24 hours after the treatment, and all larvae were dead two days after the application, with the exception of those that were near to pupate. The nests treated with TFB, DFB, and endosulfan, had all the development stages of P, erytrocephalus at end of the trial, and endosulfan showed to be the most similar treatment to the control. No new abnormally-shaped adults were found at the end of the test for TFB and DFB treatments. Therefore, when the insecticides teflubenzuron, diflubenzuron, and endosulfan were applied on their average commercial dosages for the Valle del Cauca, they showed characteristics of selectivity (in spite of the drastic conditions of the test) in terms of posterior effects over the general development of the nests of P. erythrocephalus.